Mammalian cell entry (Mce) protein of Leptospira interrogans binds extracellular matrix components, plasminogen and β2 integrin. (23rd September 2016) - Cosate, Maria Raquel; Siqueira, Gabriela Hase; de Souza, Gisele Oliveira; Vasconcellos, Silvio Arruda; Nascimento, Ana Lucia T. O.
ABSTRACT: A severe re‐emergingzoonosis, leptospirosis, is caused by pathogenic spirochetes of the genus Leptospira . Several studies have identified leptospiral surface proteins with the ability to bind ECM and plasma components, which could mediate adhesion and invasion through the hosts. It has been shown that Mce of pathogenic Leptospira spp. is an RGD (Arg‐Gly‐Asp)‐motif‐dependent virulence factor, responsible for infection of cells and animals. In the present article, we decided to further study the repertoire of the Mce activities in leptospiral biological properties. We report that the recombinant Mce is a broad‐spectrum ECM‐binding protein, capable of interacting with laminin, cellular and plasma fibronectin and collagen IV. Dose–response interaction was observed for all the components, fulfilling ligand–receptor requirements. Mce is a PLG binding protein capable to recruit this component from NHS, generating PLA in the presence of PLG activator. Binding of Mce was also observed with the leukocyte cell receptors αLβ2 [(CD11a/CD18)‐LFA‐1] and αMβ2 [(CD11b/CD18)‐Mac‐1], suggesting the involvement of this protein in the host immune response. Indeed, virulent Leptospira L1‐130 was capable of binding both integrins, whereas culture‐attenuated M‐20 strain only bind to αMβ2 [(CD11b/CD18)‐Mac‐1]. To the best of our knowledge, this is the first work to describe that Mce surface protein could mediate the attachment of Leptospira interrogans to human cell receptors αLβ2(CD11a/CD18) and αMβ2(CD11b/CD18).